2014
DOI: 10.3892/or.2014.3588
|View full text |Cite
|
Sign up to set email alerts
|

Nestin predicts a favorable prognosis in early ampullary adenocarcinoma and functions as a promoter of metastasis in advanced cancer

Abstract: Nestin exhibits stemness characteristics and is over-expressed in several types of cancers. Downstream signaling of nestin [cyclin-dependent kinase 5 (CDK5) and Ras-related C3 botulinum toxin substrate 1 (Rac1)] functions in cancer to modulate cellular behaviors. We studied the function of nestin in ampullary adenocarcinoma. Immunohistochemistry (IHC), reverse transcription-polymerase chain reaction, and cDNA microarray of nestin in ampullary adenocarcinoma was compared with normal duodenum. CDK5 and Rac1 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…High nestin expression is more common in aggressive uterine cancers, but appears to be more predictive of poor outcome in patients with lower risk, including those with early stage disease and G1/G2 endometrioid histologies with and without LVSI. These findings are consistent with the mechanistic studies of nestin and clinical outcome assessments of nestin expression in other cancers [20,22,25,26]. It is a testable and biologically relevant protein that may have utility as a triage tool to identify lower risk patients who may require more aggressive treatment.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…High nestin expression is more common in aggressive uterine cancers, but appears to be more predictive of poor outcome in patients with lower risk, including those with early stage disease and G1/G2 endometrioid histologies with and without LVSI. These findings are consistent with the mechanistic studies of nestin and clinical outcome assessments of nestin expression in other cancers [20,22,25,26]. It is a testable and biologically relevant protein that may have utility as a triage tool to identify lower risk patients who may require more aggressive treatment.…”
Section: Discussionsupporting
confidence: 81%
“…Nestin is a regulator of TGF-β [17,18] and in vitro experiments have demonstrated that it plays a role in invasion, metastasis, and angiogenesis [17,22]. The association of nestin expression with prognosis has been demonstrated in ganglioglioma, ovarian, head and neck, prostate, bladder, and pancreatic cancer [20,22,25,26], and from the present work, in uterine cancer. Nestin may have utility as a theragnostic triage companion test and opportunity for further risk stratification for clinical management.…”
Section: Discussionsupporting
confidence: 68%
“…To date, the expression of CDK5 was investigated in several cancers [ 13 , 15 , 17 ]. Higher expression of CDK5 was observed in hepatocellular carcinoma, ampullary adenocarcinoma, breast cancer, and medullary thyroid carcinoma, and Zachary et al confirmed the expression of CDK5 was upregulated in colorectal, head/neck, breast, lung, ovarian, lymphoma, prostatic, sarcoma, myeloma, and bladder cancers via the Oncomine microarray online data mining software [ 11 , 12 , 18 , 28 ]. However, downregulated expression of CDK5 was observed in gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…CDK5 regulates DNA damage response via phosphorylating Ataxia telangiectasia mutated (ATM) kinase and thereby affecting its downstream signal pathways which was crucial to progression of hepatocellular carcinoma [ 12 ]. In ampullary adenocarcinoma, over expression of nestin/CDK5 was involved in several oncogenic pathways (the activation of NOTCH, TGF-β1, or PDGFR pathways) that facilitated invasiveness of cancer [ 28 ]. In breast cancer, CDK5 takes part in epithelial-mesenchymal transition induced by TGF-β1which is vital for tumor metastasis [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…It plays a critical role in cancer cell migration, invasion, angiogenesis, and metastasis both in vitro and in vivo [12][13][14][15]. Nestin confers a poor prognosis in a number of cancers [11,[16][17][18], but had not yet been explored in uterine cancer.…”
Section: Nestin Commentarymentioning
confidence: 99%